X-ray Inspection of MIM 418 Superalloy Turbine Wheels and Defects Analysis. Issue 2 (February 2017) - Yanhong, Jing; Fubao, Yang; Daquan, Li; Hao, Li; Lin, Zhang; Dan, Li; Qiang, Zhu
Abstract: Turbine wheels produced by metal injection molding (MIM) were subjected to X-ray inspection using three different X-ray instruments, including film X-ray, real-time imaging X-ray and microfocus X-ray. One of the X-ray inspected turbine wheels was then cut and polished for defects observation using optical microscope (OM) and scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDS). The defects existing in the blades and the center of the turbine wheels were analyzed using an analysis software. The results show that under the same testing condition, the film X-ray equipment has higher sensitivity than the real-time imaging X-ray. However, the microfocus X-ray testing is not suitable to the MIM418 turbine wheels due to low power. Nondestructive testing (NDT) and metallographic observation reveal that macro-cracks are prone to forming in the center part of the turbine wheel, and the micro-defects in term of porosity in the blade are more than in the center of the sintered turbine wheel. Although heat isostatic pressing (HIP) can significantly decrease the porosity, cracks are not healed.